Textbook of Clinical Occupational and Environmental Medicine - Rosenstock, Linda and Cullen, Mark (Harcourt Brace and Company, 1994)
Comprehensive and meticulously updated throughout, this new edition makes it easy to detect, diagnose, and treat the full spectrum of problems caused by occupational or environmental factors, including physical, chemical, and biologic agents. An international cast of experts offers in-depth, authoritative guidance on clinical problems as well as the legal and regulatory issues impacting the practice of occupational and environmental medicine today.
Keywords: Industrial hygiene; Non-Fiction; Occupational diseases